Mind-Body Therapies in Childhood Cancer (2018)
Purpose of Review: Advances in the field of Pediatric Oncology have led to increased survival rates in children with cancer, and addressing the emotional well-being and quality of life of this specific population is a critical component of care. Mind-body therapies (MBTs) are an adjuvant modality of treatment that appears to have a positive impact on patient quality of life, patient mental health, and family perceptions toward illness. In this review, we describe several evidence-based MBTs, such as art therapy, meditation, prayer, music therapy, hypnosis and relaxation techniques, their use, and our personal experience with MBT in our institution. Recent Findings: Current data suggests that MBTs have been effective in decreasing symptoms related to oncologic pathology in children. Based on experience in our institution, the administration of these therapies can be expanded with the use of technology and also foster family inclusion in care, which can lead to improved quality of life for the patient and family. Further studies are warranted to ascertain the effects of MBTs in childhood cancer. Summary: MBTs are increasingly important in the care of youth with oncologic disease. It is necessary to increase the quantity and quality of research for the selection and inclusion of MBT in this population. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.